PATIENT ANXIETY LEVEL ON PANORAMIC EXAMINATION AT RSUD Dr SOEROTO NGAWI: CASE STUDY - lisnawati S. Gafar; Ildsa Maulidya Mar’athus Nasokha; Anshor Nugroho (Journal of Indonesian Anesthesiology Nursing, 2024)
ABSTRACT Bacground: Anxiety is something that often occurs in human life. Anxiety is an emotional response that arises as a reaction to a perceived threat even though the threat even though the threat is not actually real. This research includes anxiety which is divided examinations, starting from teenage patients and adult patients at the Radiology Installation at Dr Soeroto Regional Hospital, Ngawi. Patients feel anxious and panic, which can lead to repeated photos because the radiograph results are not optimal. The purpose of this paper is to determine the level of patient anxiety during panoramic examinations, to find out how radiographers act in overcoming patient anxiety during panoramic examinations. Methods: : This research is a descriptive qualitative research method with a case study approach. The research was carried out in January 2024 – September 2024 at the radiology installation at Dr Soeroto Hospital, Ngawi. The data collection was performed by observation, interviews, questionnaires, and documentation guidelines. The research subjects were 3 radiographers and 5 patients. The object of this research was a case study of patient anxiety levels during panoramic examination. The data analysis conducted by using univariate analysis, namely analyzing each variable from the research results to produce a frequency distribution and percentage for each variable. Resultl: The results of the research showed that the frequency distribution of respondents' characteristics based on age groups obtained the highest percentage, namely (40.0%), with the age range of 15-20 frequency was 2, the age range of 41-44 frequency was 2. The lowest percentage number was (20, 0%) with a total frequency was 1. The frequency distribution of respondent characteristics based on gender showed that the respondents with the highest percentage value were (60.0%) with 3 female and male respondents. Respondents with the lowest percentage value were 2 respondents (20.0%). An example of action taken to reduce patient anxiety is by inviting the patient to talk so that the patient's mind is diverted from feeling anxious do not forget to introduce yourself to the patient; and by explaining to the patient the examination procedure that will be carried out, namely a panoramic examination where the panoramic aircraft will rotate around the patient and emit x ray rays Conclusion: The conclusions that can be drawn from the research conducted by the author regarding the level of anxiety of patients during panoramic examinations at Dr Soeroto Regional Hospital, Ngawi are as follows: The level of patient anxiety during panoramic examinations at the Radiology Installation at Dr Soeroto Regional Hospital, Ngawi results obtained are based on the characteristics of respondents from the age range obtained the highest percentage value 40.0%) with the total of 4 respondents. Meanwhile, the frequency of respondents' characteristics based on gender, Thus, it can be concluded that the anxiety level of patients at Dr Soeroto Regional Hospital, Ngawi is still in the mild anxiety category. As the effort to overcome patient anxiety, it can be done by having casual communication with the patient, namely by asking about the patient's daily activities without forgetting to introduce yourself and explaining the procedures of how the panoramic too will work.